Influenza A virus ribonucleoproteins modulate host recycling by competing with Rab11 effectors - Vale-Costa, Sílvia (2016)
Influenza A virus assembly is an unclear process, whereby individual virion components form an infectious particle. The segmented nature of the influenza A genome imposes a problem to assembly because it requires packaging of eight distinct RNA particles (vRNPs). It also allows genome mixing from distinct parental strains, events associated with influenza pandemic outbreaks. It is important to public health to understand how segmented genomes assemble, a process that is dependent on the transport of components to assembly sites. Previously, it has been shown that vRNPs are carried by recycling endosome vesicles, resulting in a change of Rab11 distribution. Here, we describe that vRNP binding to recycling endosomes impairs recycling endosome function, by competing for Rab11 binding with family-interacting proteins, and that there is a causal relationship between Rab11 ability to recruit family-interacting proteins and Rab11 redistribution. This competition reduces recycling sorting at an unclear step, resulting in clustering of single- and double-membraned vesicles. These morphological changes in Rab11 membranes are indicative of alterations in protein and lipid homeostasis during infection. Vesicular clustering creates hotspots of the vRNPs that need to interact to form an infectious particle.